Collaborative Counseling to Build a Social Construct to Overcome Alcoholic Addiction - Nikmarijal, Nikmarijal; Ahmad, Bukhari (International Journal of Research in Counseling, 2024)
Alcohol consumption by teenagers is influenced by environmental factors. To overcome alcohol addiction among teenagers, a social construction needs to be built. So efforts are needed to overcome alcohol addiction, namely through collaborative counseling. In Collaborative Counseling the relationships and conversations create something different bringing together the collection, application, innovation and expansion of ideas involving working professionals from various disciplines, contexts and cultures, by detailing what they actually do every day for individuals, couples, families and groups . This research uses a Mixed Method with the Triangular Design type, namely collecting quantitative and qualitative data simultaneously. Quantitative research was conducted to answer the first research question, how addicted the sample was to alcohol during the research. By using Time-series Design with a simple interrupted Time Series approach with a sample size of 8 people. The qualitative research used in this research is a phenomenological approach, namely research that answers what certain phenomena are about. This research will also be used to interpret meaning in context. From the results obtained in this research, it was found that Collaborative Counseling was successful in eliminating addiction in the research sample.